Evaluasi Ketebalan Irisan (Slice Thickness) pada Pesawat CT-Scan Single Slice - Makmur, I Wayan Ari; Setiabudi, Wahyu; Anam, Choirul (JURNAL SAINS DAN MATEMATIKA, 2013)
An evaluation of the value of the slice thickness due to changes in tube voltage and tube current on the CT scan have been performed. The evaluation is done by making images using CT performance test phantom. Testing is done by performing three scanning on each slice. Exposure factors used were 120 kVp-60 mA, 160 mA 120-kVp, 140-kVp 60 mA, and 140 kVp 160 mA. Nominal beam width were 2 mm, 3 mm, 5 mm, 7 mm, and 10 mm. Once the axial image was obtained (on the area for slice thickness determination), then calculated the average CT number on the region of interest (ROI). After it was made graphs to determine the value of FWHM which indicates the magnitude of the thickness of the slice. From the test results obtained that changes in tube voltage and tube current does not affect the value of the thickness of the slice. Also found that the value of slice thickness for each thickness, greater than the nominal beam width. Keywords: Phantom CT Performance Test, Slice Thickness, CT-Scan Telah dilakukan evaluasi terhadap nilai slice thickness terhadap perubahan tegangan tabung dan arus tabung pada pesawat CT scan. Pengujian dilakukan dengan membuat citra menggunakan fantom CT performance test. Pengujian dilakukan dengan melakukan eksposi sebanyak tiga kali pada tiap-tiap slice. Faktor eksposi yang digunakan yaitu 120 kVp-60 mA, 120 kVp-160 mA, 140 kVp-60 mA, dan 140 kVp-160 mA. Slice thickness yang diuji adalah ketebalan 2 mm, 3 mm, 5 mm, 7 mm, dan 10 mm. Setelah didapatkan citra aksial pada bagian daerah uji slice thickness, maka diambil beberapa lokasi ROI dan dihitung rerata CT Number, kemudian nilai tersebut dibuat grafik dan ditentukan nilai FWHM yang menunjukkan besarnya slice thickness. Dari hasil pengujian diketahui perubahan tegangan tabung dan arus tabung tidak berpengaruh terhadap nilai slice thickness. Hasil pengukuran diketahui bahwa nilai slice thickness untuk masing-masing ketebalan, lebih besar dibanding nominal beam width. Kata kunci : Simulasi Monte Carlo, Percentage Depht Dose (PDD), Dose Profile, Inhomogenitas Jaringan.